Participant Action Research (PAR) for early childhood and primary education: the example of the THRIECE project - Leah O’Toole (Problemy Wczesnej Edukacji)
This paper explores the potential benefits of Participant Action Research (PAR) for early childhood and primary education. It presents the example of the Erasmus+ funded THRIECE (Teaching for Holistic, Relational and Inclusive Early Childhood Education) project, and drawing on the reflections of its participants, supports PAR as a respectful, inclusive, relevant approach to educational research that can lead to deep personal and intercultural learning. It highlights the importance of embracing the ‘messiness’ of action research, and allowing its non-linear complexity to enhance both process and outcomes. It explores the potential of PAR to allow for investigation of and value for the embodied, tacit knowledge and understandings of expert educators, supporting continuous development of practice and providing the language for educators to explain their approaches. Finally, it identifies the crucial nature of a relational approach for the success of Participant Action Research.